1984
DOI: 10.1099/00221287-130-5-1069
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of N2 Fixation and Ammonia Assimilation in Rhodopseudomonas sphaeroides f. sp. denitrificans. Role of Glutamine

Abstract: Glutamine is shown to be the effector compound for the regulation of both nitrogenase and glutamine synthetase activities in Rhodopseudomonas sphaeroides f. sp. denitr$cans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…2). These data support the idea that glutamine and/or a derivative of it plays an essential role in mediating the ammonium switch-off of nitrogenase, as implicated in several other systems (11,26,35 Posttranslational regulation of nitrogenase by covalent modification of dinitrogenase reductase through ADP-ribosylation has been described earlier for certain photosynthetic bacteria, and the present work demonstrates that a similar control system can function in nonphotosynthetic bacteria.…”
Section: Resultssupporting
confidence: 75%
“…2). These data support the idea that glutamine and/or a derivative of it plays an essential role in mediating the ammonium switch-off of nitrogenase, as implicated in several other systems (11,26,35 Posttranslational regulation of nitrogenase by covalent modification of dinitrogenase reductase through ADP-ribosylation has been described earlier for certain photosynthetic bacteria, and the present work demonstrates that a similar control system can function in nonphotosynthetic bacteria.…”
Section: Resultssupporting
confidence: 75%
“…One of the problems in assessing the regulatory effect of interstitial NH4' on nitrogenase activity in the salt marsh is that concentrations can range from 3 to 300 p.M (3,6,7,10,21,28,35), with the higher concentrations apparently occurring early in the growing season (3). Since all in situ studies in salt marshes have shown substantial rates of nitrogenase activity (26,27), microenvironments probably exist where levels of NH4' are low enough to permit N2 fixation to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Michalski and Nicholas (19) observed an increase in glutamine level during ammonium addition to a nitrogen-fixing culture of Rhodopseudomonas sphaeroides f. sp. denitrificans and concluded that the increase in glutamine concentration was responsible for the loss of nitrogenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Ammonium treatment brought about a general increase in the levels of the amino acids, whereas the effect of glutamine was transient. GS, glutamine, or metabolites related to glutamine have been proposed to regulate the switch-off of nitrogenase activity in phototrophs (7,19,37,42,44). In the present study, changes in the concentrations of glutamine, glutamate, and other amino acids of glutamate-grown cultures were monitored during switch-off of nitrogenase by ammonium, darkness, glutamine, and PMS.…”
mentioning
confidence: 99%